2007
DOI: 10.1152/ajpendo.00611.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoxia on the release of vascular endothelial growth factor and testosterone in mouse TM3 Leydig cells

Abstract: Hypoxia has been shown to stimulate the expression of vascular endothelial growth factor (VEGF), which is a major mediator for angiogenesis and vasculogenesis. During hypoxia, VEGF promotes angiogenesis in the testis. However, the effect of VEGF on the steroidogenesis of testosterone and the cell proliferation in Leydig cells is unclear. To assess the effects and the action mechanisms of hypoxia, a mouse TM3 Leydig cell line was employed in the present study. The Leydig cells were incubated in an incubator cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 47 publications
(35 reference statements)
4
30
0
3
Order By: Relevance
“…During hypoxia, VEGF promotes angiogenesis in the testis. Hypoxia, in turn, stimulates cell proliferation and testosterone release in Leydig cells via an increase of VEGF production [31]. In our study, we also found an increased VEGF immunoactivity in Leydig cells in the specimens of smokers.…”
Section: Discussionsupporting
confidence: 82%
“…During hypoxia, VEGF promotes angiogenesis in the testis. Hypoxia, in turn, stimulates cell proliferation and testosterone release in Leydig cells via an increase of VEGF production [31]. In our study, we also found an increased VEGF immunoactivity in Leydig cells in the specimens of smokers.…”
Section: Discussionsupporting
confidence: 82%
“…VEGF expression has been detected in mouse Sertoli cells, whereas its receptors are located in spermatocytes and spermatids (Nalbandian et al 2003). Hypoxia increases testosterone release in the mouse TM3 cell line mediated by increased VEGFA production (Hwang et al 2007). Interestingly, hypoxia leads to an increase in NAMPT gene expression in adipocytes and in a breast cancer cell line (Bae et al 2006, Segawa et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…We next studied the possible ligands released during hypoxia (Ghezzi et al, 1991;Ambalavanan et al, 1999;Michiels et al, 2000;Mouta Carreira et al, 2001;Hwang et al, 2007) that could stimulate GPCRs or RTKs to activate TRPC6 and mediate the hypoxia-induced intracellular Ca 2+ elevation. Treatment of cells with 3-nitrocoumarin, an agent known to inhibit PLCγ activity without affecting PLCβ, but not its inactive analog 7-OH-3-nitrocoumarin, substantially suppressed the Ca 2+ elevation (Fig.…”
Section: Activation Of Trpc6 Channels During Hypoxiamentioning
confidence: 99%